Constraining superluminal Einstein-Æther gravity through gravitational memory - Heisenberg, Lavinia; Rosatello, Benedetta; Xu, Guangzi; Zosso, Jann (Physical review, 2025)
Every emission of radiation in gravity also includes a nonwavelike component that leaves a permanent change in proper distances of the spacetime it travels through. This phenomenon is known as gravitational displacement memory. Building up on a recently developed computation framework that harnesses Isaacson’s insights on a fundamental definition of gravitational waves, we compute the leading displacement memory formula in Einstein-Æther gravity. Our analysis represents the first direct calculation of gravitational memory in a metric theory with nontrivial asymptotic vector field value. We find that an emission of scalar and vector æther waves at a propagation speed greater than the speed of tensor radiation features unprotected causal directions with a priori unbound memory buildup. Based on the results and the existing constraint of luminally propagating tensor waves, we conjecture a stringent exclusion of the superluminal parameter space of Einstein-Æther gravity.
Gesehen am 15.12.2025